Transcatheter aortic valve replacement in obese patients: procedural vascular complications with the trans-femoral and trans-carotid access routes. (23rd December 2021) - Alperi, Alberto; McInerney, Angela; Modine, Thomas; Chamandi, Chekrallah; Tafur-Soto, Jose D; Barbanti, Marco; Lopez, Diego; Campelo-Parada, Francisco; Cheema, Asim N; Toggweiler, Stefan; Saia, Francesco; Amat-Santos, Ignacio; et al.
Abstract: OBJECTIVES: Obesity may increase the risk of vascular complications in transfemoral (TF) transcatheter aortic valve replacement (TAVR) procedures. The transcarotid (TC) approach has recently emerged as an alternative access in TAVR. We sought to compare vascular complications and early clinical outcomes in obese patients undergoing TAVR either by TF or TC vascular access. METHODS: Multicentre registry including obese patients undergoing TF- or TC-TAVR in 15 tertiary centres. All patients received newer-generation transcatheter heart valves. For patients exhibiting unfavourable ileo-femoral anatomic characteristics, the TC approach was favoured in 3 centres with experience with it. A propensity score analysis was performed for overcoming unbalanced baseline covariates. The primary end point was the occurrence of in-hospital vascular complications (Valve Academic Research Consortium-2 criteria). RESULTS: A total of 539 patients were included, 454 (84.2%) and 85 (15.8%) had a TF and TC access, respectively. In the propensity-adjusted cohort (TF: 442 patients; TC: 85 patients), both baseline and procedural valve-related characteristics were well-balanced between groups. A significant decrease in vascular complications was observed in the TC group (3.5% vs 12% in the TF group, odds ratio: 0.26, 95% CI: 0.07–0.95, P = 0.037). There were no statistically significant differences between groups regarding in-hospital mortality (TC: 2.8%, TF: 1.5%), stroke (TC: 1.2%, TF: 0.4%) and life-threatening/major bleeding events (TC: 2.8%, TF: 3.8%). CONCLUSIONS: In patients with obesity undergoing TAVR with newer-generation devices, the TC access was associated with a lower rate of vascular complications. Larger randomized studies are warranted to further assess the better approach for TAVR in obese patients. Abstract : Transcatheter aortic valve replacement (TAVR) has been established as a first-line therapeutic option for high-risk and elderly patients with symptomatic severe aortic stenosis [1–3].